Management of Paediatric Cataract at Khyber Teaching Hospital Peshawar - Iqbal, Zafar; Iqbal, Arjumand; Islam, Zia ul (Journal of Postgraduate Medical Institute, 2011)
To point out the causes of cataract and aim at controlling childhod blindness. A retrospective study on 110 cases of paediatric coataract admitted to Eye A ward, KTH over a 12 month period between 1st January 2000 - 31st December 2000 was carried out. The etiology of cataract varied from developmental (60.3%), Traumatic (24%) and congenital (13.7%) to complicated (2%) cataract.